Indirect prediction of bud flushing from ex situ observation in hybrid Larch (Larix decidua x L. kaempferi) and their parents - Gauchat, Maria Elena; Pâques, Luc E. (Elsevier, 2019)
Phenology of bud burst was studied for larches (Larix) using ex situ and in situ observations. The main objective of the study was to test the possibility to predict flushing in the field (in situ) from ex situ parameters obtained in growth chambers. Several progenies of European (EL), Japanese (JL) and hybrid (HL) larches were assessed in progeny trials for dates of terminal bud flushing and of overall “greening” of the tree (proportion of green crown). Twigs collected on the same trees during the previous winter were observed under controlled environments in two growth chambers, one at 11 °C and the other at 16 °C. Dates of flushing were recorded and from these, threshold temperatures and heat-sum requirements to flush were estimated. Correlations between in situ and ex situ parameters were studied and several linear models were tested to predict in situ flushing parameters using flushing days and heat-sums from ex situ experimentation.